2013
DOI: 10.9790/4861-0420105
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Orthodontic Treatment in School Children of Karnataka State – A Survey

Abstract: Aims: To assess the awareness of Orthodontic treatment among school children in Karnataka. Settings and Design: School settings and Descriptive cross-sectional survey. Methods and Material: A crosssectional epidemiological survey was conducted in all the 30 districts of Karnataka. School children in the age group of 10-16 years were the target population. Population proportionate technique was employed for the sample size estimation. A total sample of 9505 was randomly selected from 102 schools all over Karnat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Previous studies revealed that parents who have been former orthodontic patients or are willing to undergo orthodontic treatment are more approving of this treatment for their children [8][9][10]. Malocclusion is not considered a dental problem by most parents [11]. Many factors play a major role in determining parents' perceptions and attitudes towards seeking orthodontic care for their children.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that parents who have been former orthodontic patients or are willing to undergo orthodontic treatment are more approving of this treatment for their children [8][9][10]. Malocclusion is not considered a dental problem by most parents [11]. Many factors play a major role in determining parents' perceptions and attitudes towards seeking orthodontic care for their children.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies were conducted to assess the awareness levels of oral health and need for orthodontic treatment among pre-adolescent and adolescents. [3][4][5][6] The present study was undertaken to study the levels of awareness among young adults.…”
Section: Introductionmentioning
confidence: 99%